A hybrid fuzzy approach for industry competition analysis - Valeriy Balan; Vasyl Pryimak; Inna Tymchenko (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
The paper suggests a hybrid approach to strategic diagnostics of the industry competition based on the application of M. Porter's model of five forces, tools of logical-linguistic modelling and the theory of fuzzy sets. Two complementary calculation schemes were developed to assess the level of competition in the industry. The first of them is based on fuzzy multicriteria analysis using the Fuzzy SAW method, the second is based on the construction of a logical-linguistic model with fuzzy expert knowledge bases and the use of fuzzy inference using Mamdani Fuzzy Inference System. Fuzzy numbers in triangular form with triangular membership functions are used to represent the linguistic assessments of experts, and the CoA (Center of Area) method is used to defuzzify the obtained values. The study proposes to implement a model in the form of a framework in Excel. The framework allows simulation, depending on the modification of the list of certain factors of the external environment and correction of experts' considerations. The methodological approach can be used in conducting a strategic audit of the microenvironment of an enterprise, in competitive analysis, in strategic planning of enterprise activities as a basis for the development and implementation of effective competitive strategies.
Keywords: C51; C63; D04; 330; Fuzzy Sets; Fuzzy Multicriteria Analysis; Porter's Force Assessment Model; Fuzzy SAW-method; Logical-linguistic Model; Fuzzy Knowledge Bases; Mamdani Fuzzy Inference System